Marine ecosystem-based management in practice : different pathways, common lessons - Wondolleck, Julia Marie; Yaffee, Steven L. (Imprint : Island Press, 2017)
The authors are hopeful. Rather than lamenting the persistent conflicts in global marine ecosystems, they instead sought out examples where managers were doing things differently and making progress against great odds. They interviewed planners, managers, community members, fishermen, and environmentalists throughout the world to find the best lessons for others hoping to advance marine conservation. Their surprising discovery? Successful marine management requires not only the right mix of science, law, financing, and organizational structure, but also an atmosphere of collaboration--a comfortable place for participants to learn about issues, craft solutions, and develop the interpersonal relationships, trust, and understanding needed to put plans into action. This volume is the first practical guide for the marine conservation realm. In a unique collection of case studies, the authors showcase successful collaborative approaches to ecosystem-based management. The authors introduce the basic concepts of ecosystem-based management and five different pathways for making progress from community to multinational levels. They spotlight the characteristics that are evident in all successful cases --the governance structures and social motivations that make it work. Case analyses ranging from the Gulf of Maine to the Channel Islands in Southern California comprise the bulk of the book, augmented by text boxes showcasing examples of guiding documents important to the process. They devote several ending chapters to discussion of the interpersonal relationships critical to successful implementation of marine ecosystem-based management. The book concludes with a discussion of the implications for policy and on-the-ground practice. This book offers a hopeful message to policy makers, managers, practitioners, and students who will find this an indispensable guide to field-tested, replicable marine conservation management practices that work. - Resumé vydavatel